2014
DOI: 10.1117/12.2083585
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products in hemodialysates as fluorescent and optical absorption markers of patients mortality

Abstract: Hemodialysate (HD) samples collected from the end stage renal disease patients (ESRD Pts) were used for search for possible correlation between the intensity of HD visible auto-fluorescence (VF) detected at 420 nm as well as their optical absorption at 320 nm and the mortality events among the Pts. Previous but strongly promising correlations has been found in both cases which deserve further supplementation and examination. Investigation of possible influence of quenchers onto the VF intensity has been carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…1,5 It has also been observed that the visible°uorescence (VF) intensity in hemodialysates correlates with typically high mortality index among ESRD patients and could be remarkably higher if measured in the hemodialysates of the ESRD patients who died later on. 6 The same phenomenon can be traced also in the hemodialysate speci¯c absorption measurements. 6 The monitoring is going on.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…1,5 It has also been observed that the visible°uorescence (VF) intensity in hemodialysates correlates with typically high mortality index among ESRD patients and could be remarkably higher if measured in the hemodialysates of the ESRD patients who died later on. 6 The same phenomenon can be traced also in the hemodialysate speci¯c absorption measurements. 6 The monitoring is going on.…”
Section: Introductionmentioning
confidence: 77%
“…6 The same phenomenon can be traced also in the hemodialysate speci¯c absorption measurements. 6 The monitoring is going on.…”
Section: Introductionmentioning
confidence: 77%